(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. This study aimed to investigate the protective effect of aerial parts of the Tribulus terrestris L extract on acute kidney injury (AKI) induced by ischemia for 30 minutes and reperfusion for 24 hours in rats. Materials and Methods. Ten male Sprague-Dawley rats in the AKI and 10 in the Tribulus terrestris groups received the extract solvent and extract of the plant (11 mg/kg), respectively, for 13 days (oral administration). On day 14, ischemia for 30 minutes and reperfusion for 24 hours were induced on the rats. In the last 6 hours of the reperfusion period (24 hours), urine samples were collected in metabolic cages. At the end of this period, blood samples were also taken to determine plasma urea nitrogen, creatinine, and electrolyte concentrations. The kidney tissues were collected for measuring the level of oxidative stress and histological studies. They were compared with the sham operation group and a control group with normal diet and no operation. Results. In the Tribulus terrestris group, the increase in plasma creatinine and urea nitrogen concentrations was significantly less following reperfusion, and their values reached the same level as that in the sham group. Creatinine clearance and urine osmolarity in the Tribulus terrestris group was higher in comparison with the AKI group, whereas sodium absolute excretion, fractional excretion of potassium, oxidative stress, and cellular damages were less. Conclusions. Oral administration of Tribulus terrestris extract for 2 weeks can decrease kidney functional disturbance, oxidative stress, and cellular damages following reperfusion injury in rats.